Influence of the size and degree of conservation of remnants of the Atlantic rain forest on chiropteran assemblages - Daniel Paulo de Souza Pires; Cristina Vargas Cademartori (Acta Biológica Catarinense, 2018)
Reduction in the size and loss of the quality of habitats are considered the greatest threats to bat species. Aiming to complement information, the objective of this study was to evaluate, from compiled data, the influence of the size of forest fragments and their degree of conservation on the richness and composition of chiropteran fauna in the Atlantic rain forest. A total of 33 publications on Chiroptera in the Atlantic rain forest was reviewed and a list of 86 species was extracted from them. The size of forest fragments exhibited positive and significant relationship with the total number of Relatively Common Species, Rare Species, Not Generalist species and with richness. Positive and significant relationship was observed between degree of conservation of the forest fragments and the total number of Rare Species, of Not Generalist species and with richness. The results here presented indicate that large and well-conserved fragments of Atlantic rain forest should be the priority when the intention is to maintain a high richness of Chiroptera and of Rare Species and Not Generalist Species.